Strength, jump heights and physical characteristics of young male basketball players by their positions - Adigüzel, N. S. (Journal of Education and Training Studies, 2019)
The aim of the study is to compare isokinetic leg strengths and jump performances of basketball players playing at different positions. A total of 34 basketball players (guards (n=13), forwards (n=13) and centers (n=7)) from 17 teams of Turkish Basketball Development League participated in the study. The isokinetic strength tests were performed for the dominant limb at two different angular speeds (60°s-1 and 180°s-1) and the extensor and flexor peak torques (EPT and FPT) were recorded. The strengths produced according to weight were taken as relative EPT and FPT. Jump tests were performed in three categories: free jump, 120° squat jump and active jump. Multivariate variance analysis (ANOVA) was used to compare players' scores in strength and jump tests by their positions. In the comparison of the positions, the guards were shorter and slimmer than the forwards and centers (p <0.05), and they were found to have less BMI values than the centers. The absolute strength values obtained with knee extension peak torques for both angular velocities were higher in the centers than the guards (p <0.05). There was no statistically significant difference in the relative strength values. Moreover, no statistically significant difference was found between the groups for other parameters and all jump parameters (p> 0.05). Consequently, it can be stated that there are physical differences among high-level young basketball players by their positions and absolute quadriceps strengths of the centers may be higher than of the guards.